Điều kiện: x + 3 ≥ 0 6 − x ≥ 0 ⇔ x ≥ − 3 x ≤ 6 ⇔ − 3 ≤ x ≤ 6
Đặt: x + 3 − 6 − x = t
⇔ ( x + 3 − 6 − x ) 2 = t 2 ⇔ x + 3 + 6 − x − 2 x + 3 6 − x = t 2
⇔ 2 x + 3 6 − x = 9 − t 2 ⇔ x + 3 6 − x = 9 − t 2 2 ( − 3 ≤ t ≤ 3 )
Khi đó, phương trình trở thành:
t = 3 + 9 − t 2 2 ⇔ t 2 + 2 t − 15 = 0 ⇔ t = 3 ( t m ) t = − 5 ( k t m
Với t=3 ⇒ x + 3 − 6 − x = 3 ⇔ x + 3 = 3 + 6 − x
⇔ x + 3 = 9 + 6 6 − x + 6 − x ⇔ 2 x − 12 = 6 6 − x
⇔ x − 6 = 3 6 − x ⇔ x − 6 ≥ 0 x 2 − 12 x + 36 = 9 6 − x
⇔ x ≥ 6 x 2 − 3 x − 18 = 0 ⇔ x ≥ 6 x = − 3 ( l ) x = 6 ( t m ) ⇔ x = 6
Vậy tập nghiệm của phương trình là S = 6
Đáp án cần chọn là: C